Understanding the parental involvement in promoting an effective orientation and mobility acquisition among visually impaired children within the expanded core curriculum in Lahore, Pakistan - Malik, Shazia; Abdul Manaf, Umi Kalthom; Ahmad, Nor Aniza; Ismail, Maimunah (Universiti Putra Malaysia Press, 2017)
This proposed for a research be carried out towards understanding the parental involvement in promoting an effective orientation and mobility (O&M) acquisition among visually impaired children within the expanded core curriculum in Lahore, Pakistan. Orientation and mobility skills are deemed important in preparing visually impaired children towards their independence. Although O&M skills are considered as one of the main components of the expanded core curriculum for visually impaired children, these skills, however, are not explicitly integrated into the expanded core curriculum. As a result, M&O skills are found less acquired by the visually impaired children in Lahore, Pakistan. Moreover, the literature has also shown that Pakistani visually impaired children are experiencing a lack of parental involvement in their O&M skills acquisition, although it is widely recognized that parental involvement is essential for such skills acquisition. Due to the lack of research on parental involvement in the O&M skills acquisition among visually impaired children in Pakistan, a study, is proposed to be conducted to gain understanding on the matter through interviews with the parents of visually impaired children at two secondary level schools in Lahore, Pakistan. A semi-structured interview strategy will be employed to provide more insights into the roles of parents towards the acquisition of O&M skills among their visually impaired children in Lahore, Pakistan. This proposal further discusses the methodology deemed appropriate for this study.